2003
DOI: 10.1108/03321640310451971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the electro‐magnetic stirring on the boundary layer of a molten steel pool

Abstract: Electro‐magnetic stirrers, applied to the mold of a continuous caster, induces electromagnetic forces that influence the steel flow pattern modifying the casting parameters. The steel quality has been highly improved by the application of this magneto‐hydro‐dynamic (MHD) technique. Anyway, the complexity of the MHD interaction made difficult the complete comprehension of the factors that contribute to eliminate the defects due to the inclusions in the cast products. The optimization of the MHD techniques is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Liu et al (2012) found that tangential velocity of the liquid steel increases with the increase in current intensity and frequency. Fabbri et al (2003) discussed the influence of M-EMS on boundary layer flow of liquid steel. Ren et al (2015a, 2015b) considered solidification while modelling electromagnetic stirring in round bloom mold.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2012) found that tangential velocity of the liquid steel increases with the increase in current intensity and frequency. Fabbri et al (2003) discussed the influence of M-EMS on boundary layer flow of liquid steel. Ren et al (2015a, 2015b) considered solidification while modelling electromagnetic stirring in round bloom mold.…”
Section: Introductionmentioning
confidence: 99%